2021
DOI: 10.1111/mec.15818
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐scale genetic structure reflects limited and coordinated dispersal in the colonial monk parakeet, Myiopsitta monachus

Abstract: The genetic structure of animal populations has considerable behavioural, ecological and evolutionary implications and may arise from various demographic traits. Here, we use observational field data and molecular genetics to determine the genetic structure of an invasive population of monk parakeets, Myiopsitta monachus, at a range of spatial scales, and investigate the demographic processes that generate the observed structure. Monk parakeets construct large nests that can house several pairs occupying separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 135 publications
2
29
1
Order By: Relevance
“…Unlike the other parrot species, monk parakeets build their own nests, a large structure of sticks located in trees or human construction such as pylons [14]. These nests normally include several chambers, each occupied by a different pair or kin groups that cooperate in the maintenance, breeding, and defense of the whole colony [14][15][16]. Monk parakeets usually tolerate the presence of other species in their nests, despite the fact that certain tenants may aggressively usurp active chambers [15].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the other parrot species, monk parakeets build their own nests, a large structure of sticks located in trees or human construction such as pylons [14]. These nests normally include several chambers, each occupied by a different pair or kin groups that cooperate in the maintenance, breeding, and defense of the whole colony [14][15][16]. Monk parakeets usually tolerate the presence of other species in their nests, despite the fact that certain tenants may aggressively usurp active chambers [15].…”
Section: Introductionmentioning
confidence: 99%
“…This period of sampling was chosen because natal dispersal by juveniles in their first year, if present, has already taken place and the birds are ready to breed, building or maintaining nests, or actively breeding [30]. Monk parakeets are sedentary, long-lived, and use the nests year-round for roosting and breeding for multiple years [27,31]. The species is also colonial, building large compound nests [27].…”
Section: Methodsmentioning
confidence: 99%
“…Monk parakeets are sedentary, long-lived, and use the nests year-round for roosting and breeding for multiple years [27,31]. The species is also colonial, building large compound nests [27]. About 80% of birds breed in the same nest in successive years, and dispersing adult birds move an average distance of just 37 m [27], removing any bias of using two years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Monk Parakeet, sexual monogamy was shown in their native and invasive sites [188], while a later study found evidence for extra pair paternity in their native range in Argentina and intra-brood parasitism at invasive sites [189]. A recent study on their breeding colonies showed fine-scale genetic structure, high breeding site fidelity, absence of inbreeding, and female-biased natal dispersal by genotyping individuals [190].…”
Section: Behavioural Ecologymentioning
confidence: 99%